Coculture of dorsal root ganglion neurons and differentiated human corneal stromal stem cells on silk‐based scaffolds. Issue 10 (25th May 2015) - Wang, Siran; Ghezzi, Chiara E.; White, James D.; Kaplan, David L.
Abstract Corneal tissue displays the highest peripheral nerve density in the human body. Engineering of biomaterials to promote interactions between neurons and corneal tissue could provide tissue models for nerve/cornea development, platforms for drug screening, as well as innovative opportunities to regenerate cornea tissue. The focus of this study was to develop a coculture system for differentiated human corneal stromal stem cells (dhCSSCs) and dorsal root ganglion neurons (DRG) to mimic the human cornea tissue interactions. Axon extension, connectivity, and neuron cell viability were studied. DRG neurons developed longer axons when cocultured with dhCSSCs in comparison to neuron cultures alone. To assess the mechanism involved in the coculture response, nerve growth factors (NGF) secreted by dhCSSCs including NGF, brain‐derived neurotrophic factor (BDNF), glial cell‐derived neurotrophic factor (GDNF), and neurotrophin‐3 were characterized with greater focus on BDNF secretion. DhCSSCs also secreted collagen type I, an extracellular matrix molecule favorable for neuronal outgrowth. This coculture system provides a slowly degrading silk matrix to study neuronal responses in concert with hCSSCs related to innervation of corneal tissue with utility toward human corneal nerve regeneration and associated diseases. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 3339–3348, 2015.